Transporter-Mediated Solutes Uptake as Drug Target in Plasmodium falciparum - Monteiro Júnior, Júlio César; Krüger, Arne; Palmisano, Giuseppe; Wrenger, Carsten (Frontiers in Pharmacology, 2022)
Malaria remains a public health problem with still more than half a million deaths annually. Despite ongoing efforts of many countries, malaria elimination has been difficult due to the resistance against most traditional drugs, including artemisinin compounds - the most potent antimalarials currently available. Therefore, the discovery and development of new drugs with novel mechanisms of action to circumvent resistances is urgently needed. In this sense, one of the most promising areas is the exploration of transport proteins. Transporters mediate solute uptake for intracellular parasite proliferation and survival. Targeting transporters can exploit these processes to eliminate the parasite. Here, we focus on transporters of the Plasmodium falciparum infected red blood cell studied as potential biological targets and discuss published drugs directed at them.